Depth and structure of international news in Swedish press 1974 - Hedman, Lowe (Uppsala University, 1983)
The material has been collected from 13 Swedish dailies (Aftonbladet, Expressen, Göteborgs-Posten, Dagens Nyheter, Svenska Dagbladet, Arbetet, Kvällsposten, Västerbottens-Kuriren, Norrtelje Tidning, Dala-Demokraten, Gotlands Allehanda, Västernorrlands Allehanda and Östersunds-Posten). The issues that the study intends to elucidate is: amount of international material; amount of international material in comparison with the total material; differences between various newspapers; distribution among various countries, international organizations etc.; type of events; space allocated to different types of events; origin of news, news sources; sources referred to when using foreign material; one-sided, diversified or ´neutral´ reports; use of summaries merely; the extent of background descriptions, explanations, analyses etc.

The material has been collected from 13 Swedish dailies (Aftonbladet, Expressen, Göteborgs-Posten, Dagens Nyheter, Svenska Dagbladet, Arbetet, Kvällsposten, Västerbottens-Kuriren, Norrtelje Tidning, Dala-Demokraten, Gotlands Allehanda, Västernorrlands Allehanda and Östersunds-Posten). The issues that the study intends to elucidate is: amount of international material; amount of international material in comparison with the total material; differences between various newspapers; distribution among various countries, international organizations etc.; type of events; space allocated to different types of events; origin of news, news sources; sources referred to when using foreign material; one-sided, diversified or ´neutral´ reports; use of summaries merely; the extent of background descriptions, explanations, analyses etc.
Bakgrund och struktur i utrikesmaterial i svensk press 1974
Keywords: Media; Media; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap